Jenis Fungi Akuatik yang Dapat Menginfeksi Ikan Patin (Pangasius hypophthalmus Sauvage.) yang Dipelihara di Akuarium - Atira Atira (Biocelebes, 2012)
The objective of this research is to find out aquatik fungus species on catfish in the aquarium. The research was conducted by laboratory experiments using surveillance design method. The testing parameter is aquatik fungus species that infection on catfish. Additional experimental data obtained is the water quality (DO, pH, temperature, ammoniac, and nitrate). Experimental resuls show that aqutik fungus species on the is S. parasitica. Key words: Aquatik fungus Saprolegnia parasitica, vival, catfish.